Bacterial growth conditions affect quality of GFP expressed inside inclusion bodies - Peternel, Špela (Acta chimica slovenica, 2009)
As it was shown in our previous studies, significant amount of proteins trapped inside bacterial inclusion bodies (IBs) can be properly folded. Properly folded, functional proteins can be recovered from such IBs with extraction in mild, non-denaturing conditions. Such IBs were designated non-classical inclusion bodies (ncIBs). They are easy and practical resource for extraction of active proteins. In the present study, factors influencing the quality of the target protein inside IBS were studied. Green fluorescent protein (GFP) was used as the model protein, as its proper folding (activity) can be easily monitored by fluorescence. Various growth conditions for bacterial cultivation were tested in order to increase accumulation of active (fluorescent) GFP inside ncIBs. Temperature and induction regime were recognized as very important factors affecting the growth of the bacteria Escherichia coli, as well as recombinant protein yield and protein folding. Decreasing the growth temperature resulted in higherfinal biomass production and slower bacterial metabolismč therefore the percentage of correctly folded target protein inside the cell was higher. In addition, the induction regime also influenced protein folding and immediate induction was found to be more suitable for production of GFP. Our studies confirm that optimization of bacterial growth conditions at all levels is very important for the productionof high quality recombinant protein.
Keywords: bacteria; bakterije; biokemija; biotechnology; biotehnologija; Escherichia coli; fluorescenca; molecular biology; molekularna biologija; protitelesa